Fibre reinforced cementitious composites - Bentur, Arnon (Modern concrete technology series, 2007)
"The second edition brings together in one volume the latest research development in this rapidly expanding area. The book is split into two parts. The first part is concerned with the mechanics of fibre reinforced brittle matrices and the implications for cementitious systems. In the second part the authors describe the various types of fibre-cement composites, discussing production processes, mechanical and physical properties, durability and applications. Two new chapters have been added, on fibre specification and structural applications."--Jacket.